Sampling Efficiency in Spatially Varying Soils for Slope Stability Assessment - Yajun Li; Cheng Qian; Kang Liu (Advances in Civil Engineering)
Site investigations are usually carried out in geotechnical engineering to track the range of design parameters. Due to the inherent soil spatial variability and usually limited scope of site exploration programs, the design parameters are usually uncertain at locations where test samples are not taken. This uncertainty often propagates to the response of geotechnical structures such as soil slopes. This paper developed a conditional simulation framework to investigate the sampling efficiency (i.e., sampling location and sampling distance) in designing slopes in spatially varying soils. A performance-based sampling efficiency index is proposed to achieve this. It is found that the optimal location to take vertical samples are in the vicinity of slope crest to slope midpoint and the optimal distance within a limited exploration scope is such that the additional sample subdivides the influence domain to either side of the first vertical sample.